Incidence of hospitalizations related to Lyme disease and other tick-borne diseases using Discharge Abstract Database, Canada, 2009-2021. - Salima Gasmi; Nicholas H Ogden; Annie-Claude Bourgeois; Maria Elizabeth Mitri; Peter Buck; Jules K Koffi (PLoS ONE)
To estimate rates of hospitalizations for tick-borne diseases (TBDs) in Canada, retrospective analysis was conducted to determine the incidence of patients diagnosed with TBDs during their hospital stay in Canada, and describe demographic characteristics, temporal trends and geographic distributions, from 2009 through 2021. Codes from the International Classification of Diseases, Tenth Revision (ICD-10-CA) were used to capture diagnoses of TBDs in the Discharge Abstract Database (DAD) in Canadian hospitals. From 2009 through 2021, 1,626 patients were diagnosed with TBDs during their hospital stay. Of these, 1,457 were diagnosed with Lyme disease (LD), 162 with other TBDs, and seven were diagnosed with more than one TBD. Annual hospitalization counts for LD showed a significant increase from 50 in 2009 to 259 in 2021 (incidence rate per 100,000 population of 0.1 and 0.7, respectively). Epidemiologic patterns for hospitalized LD cases, including increases and variation in annual incidences, seasonality, demographics and geographic distribution, are consistent with those elucidated in national LD surveillance data. Amongst 162 patients diagnosed with other tick-borne diseases, discharge diagnoses were: rickettsiosis (32.7%), spotted fever due to rickettsia rickettsii (23.5%), tularemia (21.0%), babesiosis (8.6%), other tick-borne viral encephalitis (6.2%), tick-borne relapsing fever (4.9%), and Colorado tick fever (0.6%). Annual incidence increased only for rickettsiosis from 3 to 12 patients over the study period. Monitoring the data of hospitalizations using the DAD provided insights into the burden of emerging TBDs, the severity of illnesses and the population most at risk.